Transformações paisagísticas na região do marco zero na cidade de Londrina - Paraná : uma análise hemeróbica - Pinheiro, Ana Cláudia Duarte (2024)
Resumo: This research was done under the methodology named hemeroby Its purpose is to examine and determine the level of the technological interference which were imposed to the landscape changes that occurred in the East area of Londrina city, which is located in Parana State, Brazil In particular, the areas studied were the following landscape units: Marco Zero (Zero Mark) in the city of Londrina, a business complex also called Marco Zero and a stream named Água das Pedras (Stone Waters) This research demanded a photographic record as a field activity and enabled us to identify the existence of a hostile environment, which is a typical reality in urban peripheries due to the existing social disparities The Landscape Units and their Subunits were identified in detail as one of the busiest areas in the city perhaps due to the high population density, or as a result of the existence of important public facilities for the metropolitan region Besides, it is close to the central area of the city Landscape studies can provide contributions in order to improve environmental quality and indicate the need for transformations in certain areas Therefore, we elaborated a system of classification that allowed us to indicate the level of hemeroby from each Landscape Unity, according to the degree of technological dependence that each of them reach The totality of the field of study shows significant disparities concerning the use and division of urban land that, many times, reflect individual advantages to the detriment of a large part of the society which suffers the consequences of actions that accentuate already troubled relations The diverse realities, such as human, social and landscape are presented in cartographic documents and images The mult iple concept ions of real ity and the convergence and complementarity f rom both areas presented here (Geography and Law) permeated by History and by other scient if ic f ields are indicators that express the way to try to understand the path of the transformat ion that were imposed to North Paraná that was so host i le in the beginning of the 2th century and so urban and developed in the thi rd millennium